Magneto-plasmonic nanostars for image-guided and NIR-triggered drug delivery - Tomitaka, Asahi (Sci Rep, 2020)
Smart multifunctional nanoparticles with magnetic and plasmonic properties assembled on a single nanoplatform are promising for various biomedical applications. Owing to their expanding imaging and therapeutic capabilities in response to external stimuli, they have been explored for on-demand drug delivery, image-guided drug delivery, and simultaneous diagnostic and therapeutic (i.e. theranostic) applications. In this study, we engineered nanoparticles with unique morphology consisting of a superparamagnetic iron oxide core and star-shaped plasmonic shell with high-aspect-ratio gold branches. Strong magnetic and near-infrared (NIR)-responsive plasmonic properties of the engineered nanostars enabled multimodal quantitative imaging combining advantageous functions of magnetic resonance imaging (MRI), magnetic particle imaging (MPI), photoacoustic imaging (PAI), and image-guided drug delivery with a tunable drug release capacity. The model drug molecules bound to the core-shell nanostars were released upon NIR illumination due to the heat generation from the core-shell nanostars. Moreover, our simulation analysis showed that the specific design of the core-shell nanostars demonstrated a pronounced multipolar plasmon resonance, which has not been observed in previous reports. The multimodal imaging and NIR-triggered drug release capabilities of the proposed nanoplatform verify their potential for precise and controllable drug release with different applications in personalized medicine.